A simple approach for a spatial terrestrial exposure assessment of the insecticide fenoxycarb, based on a high‐resolution landscape analysis. Issue 11 (29th July 2016) - Thomas, Kai; Resseler, Herbert; Spatz, Robert; Hendley, Paul; Sweeney, Paul; Urban, Martin; Kubiak, Roland
Abstract: BACKGROUND: The objective was to refine the standard regulatory exposure scenario used in plant protection product authorisations by developing a more realistic landscape‐related GIS‐based exposure assessment for terrestrial non‐target arthropods. We quantified the proportion of adjacent off‐target area in agricultural landscapes potentially exposed to insecticide drift from applications of the active substance fenoxycarb. High‐resolution imagery, landscape classification and subsequent stepwise analysis of a whole landscape using drift and interception functions were applied to selected areas in representative fruit‐producing regions in Germany. RESULTS: Even under worst‐case assumptions regarding treated area, use rate and drift, less than 12% of the non‐agricultural habitat area would potentially be exposed to fenoxycarb drift above regulatory acceptable concentrations. Additionally, if the filtering effect of tall vegetation were taken into account, this number would decrease to 6.6%. Further refinements to landscape elements and application conditions indicate that less than 5% of the habitat area might be exposed above regulatory acceptable concentrations, meaning that 95% of the non‐agricultural habitat area will be unimpacted (i.e. no unacceptable effects) and can serve as refuge for recolonisation. CONCLUSION: Approaches and tools are proposed for standardisable and transparent refinements in regulatory risk assessments on the landscape level. © 2016 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.